Comparative effectiveness of treatment modalities in non-metastatic gastric adenocarcinoma: a propensity score matching analysis of the National Cancer Database - Manish A Shah; Afsaneh Barzi; Dongyun Yang; Anthony W Kim; Sarmad Sadeghi (BMJ Open Gastroenterology)
Background While addition of chemotherapy and radiation to surgery improves the outcomes of non-metastatic gastric adenocarcinoma (GAC), the best treatment strategy remains controversial.Methods To determine the effectiveness of different strategies in patients with curative surgery, we performed an analysis of GAC patients in National Cancer Database. Propensity score method was used to control for imbalances in the confounders. Overall survival (OS), the primary outcome, was analysed using Cox proportional hazard model and Kaplan-Meier curves.Results Patients diagnosed with GAC, from 2004 to 2013, were included in this analysis and grouped according to their treatment: surgery alone (15 184), chemoradiation in the neoadjuvant (6000) or adjuvant setting (7953), and perioperative chemotherapy (PCh; 3745) or adjuvant chemotherapy (ACh; 3000). Compared with surgery alone, all adjunctive therapies resulted in an improvement in OS; neoadjuvant chemoradiation (NACRT): HR 0.9 (95% CI: 0.84 to 0.97), PCh: HR 0.73 (95% CI: 0.68 to 0.79), adjuvant chemoradiation (ACRT): HR 0.71 (95% CI: 0.67 to 0.75), and ACh: HR 0.86 (95% CI: 0.8 to 0.93). Excluding patients with surgery only, we compared different strategies to PCh. In patients with distal GAC, ACRT resulted in improved OS, (HR 0.89; 95% CI: 0.796 to 0.996), p=0.042. In patients with proximal GAC, NACRT was inferior to PCh, HR 1.101 (95% CI: 1.006 to 1.204), p=0.036.Conclusion In this real world population, addition of chemotherapy and radiation to surgery was associated with better OS. Radiation therapy may have a role in patients with distal GAC. Future research can elucidate patient, tumour, and treatment factors that necessitate the inclusion and sequence of radiation therapy in this population.